The judicial weighting test as a multicriterial exam: an analysis based on three judicial weighting models - Sotomayor Trelles, José Enrique (2017)
This paper proposes an analytic framework for the balancing or weighing test, as an instance of a Multiple-Criteria Decision Analysis (MCDA), like the ones used in disciplines like management or operations research. The change in perspective allows for an enrichment of our comprehension concerning the test, and permits an increment in its pretentions of rationality in the process of solving conflicts, in which is necessary to arrive to an optimal solution. In the first section we propose a conceptual framework concerning the development of MCDA models. Then we show three models of balancing tests proposed in the specialized literature, one of which is the model proposed by Robert Alexy. Finally, departing from a comparison between constitutional balancing and the reasonableness test, used by Indecopi, we present a complex model of balancing, which counts with two perspectives: one synchronic, and the other diachronic.